Reconstruction of full thickness chest wall defects. - Morgan, R F (1988)
Over the last 5 years, 14 patients were treated by wide en bloc resection of chest wall tumors with primary reconstruction. There were nine females and five male patients with an age range of 31-77 years. All patients had a skeletal resection of the chest wall. An average of 3.9 ribs were resected in the patients treated. In three patients a partial sternectomy was carried out in conjunction with the rib resections. Chest wall skeletal defects were reconstructed with Prolene mesh, which was placed under tension. Soft tissue reconstruction utilized selected portions of the latissimus dorsi musculocutaneous territory with fasciocutaneous extensions beyond the muscle itself. Primary healing was obtained in all patients and secondary procedures were not required. The average hospitalization was 23 days. All patients survived the resection and reconstruction and were alive 30 days after operation. In selected patients the preservation of a portion of the innervated muscle in situ or the transfer of the muscle with the preservation of its resting length has maintained the majority of the muscle function.